Kömürün mineral içeriğinin özelliklerine etkisi - Açma, Hanzade (Fen Bilimleri Enstitüsü, 1999)
Türkiye enerji ihtiyacının büyük bir kısmını linyit kömüründen sağlamaktadır. Ülkemizde düşük değerli, yani nem ve mineral madde içeriği yüksek, ısıl değeri düşük olan linyitlerden kaliteli linyitlere kadar çok çeşitli linyitler bulunmaktadır ve düşük değerli linyitlerin toplam rezerv içindeki payı oldukça yüksektir. Yenilenemeyen bir enerji kaynağı olması nedeniyle linyitlerin mümkün olan en yüksek verimle değerlendirilmesi gerekmektedir. Yakıt fiyatlarının artması ve enerji kaynaklarının sınırlı oluşu, mevcut kaynakların daha verimli kullanılmasını gerektirmektedir. Uygun koşulların sağlanmadığı yakma sistemlerinin kullanılması yenilenemeyen bir fosil enerji kaynağı olan kömürden yararlanma olanağını önemli ölçüde düşürmekte ve çevre kirliliğine yol açmaktadır. Kömür yakma sistemlerinin doğru tasarlanabilmesi ve en uygun yakma koşullarının seçilebilmesi için, kömürün yanma mekanizmasının bilinmesi gereklidir. Kömürün mineral maddesi, katalitik etkisi nedeniyle yanma kinetiğini etkileyen önemli bir faktördür. Türk linyitlerinin mineral içeriklerinin yüksek olması, bu konunun ülkemiz açısından önemini artırmaktadır. Bu çalışmada, kömürün mineral içeriğinin yanma özelliklerine etkisini incelemek amacıyla Türkiye'nin 25 değişik yöresinden toplanmış, farklı fiziksel ve kimyasal özelliklere sahip linyit numunelerine ilave olarak turba, taşkömürü ve antrasit numuneleri ile çalışılmıştır. Orijinal ve mineral maddesi giderilmiş linyit numuneleri ile onlardan elde edilen yankoklann, turba, taşkömürü ve antrasit numunelerinin TG analizleri oksitleyici ortamda gerçekleştirilmiş, elde edilen yanma profillerinden belirlenen veriler, bir bilgisayar programı yardımıyla değerlendirilmiş ve altı farklı hesaplama yöntemi ile 20 teorik model uygulamak suretiyle numunelerin yanma özellikleri araştırılmıştır. Linyit, turba ve antrasit numunelerine bazı metal bileşikleri ilave edilerek yanma özelliklerine olan etkileri incelenmiştir. Mineral madde içeriğinin kömür numunelerinin ve yankoklann yanma özelliklerini önemli ölçüde etkilediği sonucuna varılmıştır.

Burning coal in order to generate heat can be traced back at least as far as the 1 2th century; and some studies of combustion mechanisms-at that time mostly concerned with prevention of dust explosions in coal mines-began to be undertaken almost 150 years ago. Since then, however, and more especially since World War II, such more fundamental investigations have come to centre on how coal burns in different combustion systems, and have therefore focussed attention on phenomena associated with combustion of single particles and particle 'clouds' as well as on combustion in various types of fixed and fluidized fuel beds. How and how fast a coal burns depends upon the nature and composition of the coal, on the form in which it is burned, and on ambient combustion conditions. Conceptually, the events that lead to combustion when a coal particle is progressively heated in an oxygen-rich atmosphere can be divided into three stages, viz. a) Pyrolysis, with evolution of volatile matter and consequent charring of the particle; b) Ignition and combustion of vaporized hydrocarbons; and c) At sufficiently high temperatures- but even then only if sufficient oxygen can reach the particle surface- ignition and burning of the residual solid particle itself. However, linkages between these three stages depend, phenomenologically as well as kinetically, upon particle size, heating rates and char porosity. Although of considerable practical importance because it affects the length and stability of a flame, very few details respecting the combustion of volatile matter are know. In combustion studies it is usually assumed that vaporized hydrocarbons react rapidly to form CO and hydrogen, and that the rate-determining step is the slower burn-up of CO. In order to estimate the burning time of volatile matter, it is therefore generally supposed that C"Hm+l/2 nÛ2 > n CO +1/2 m H2 (I) and subsequent reactions are treated as combustion of CO and H2 in whatever kinetic terms are considered to be appropriate in the particular case. But the rates at which volatile matter discharges from the pyrolyzing coal particle-in effect, the rates at which the fresh coal particle itself heats up-also determines how quickly the charred particle will ignite and how it will thereafter burn. XV During char oxidation, the reactant, usually oxygen, diffuses from bulk phase through the boundary-layer to the surface of the particle and into the particle's pore system. The oxygen reacts with carbon in the pore walls producing CO and CO2. The CO can react in the gas phase in the vincinity of the particle in some combustion regimes to form CO2, which further reacts with the carbon in the char. Characterization of a universal intrinsic kinetic reactivity per active site, applicable for all chars, and the relationship between active site concentration and measurable structural coal or char properties, are prominent research goals. Because of the local depletion of carbon in the solid phase, the pore structure of the solid evolves spatially and temporally, affecting available surface area, active site concentrations and pore diffusional characteristics. The rate of char oxidation becomes probably the most important parameter governing the burn-out behaviour of coal. Its measurement though is complicated by a number of factors including I) variations in coal structure, ii) diffusion of rectans, iii) particle size effects, iv) pore diffusion, v) catalysis by minerals, vi) changes in surface area during the reaction, vii) fragmentation of the char, vii) temperature and pressure effects. Coal is a complex mixture of organic and inorganic materials. Mineral matter is generally considered to be the sum of all inorganic minerals (discrete phases) and elements that are present in coal. Thus, all elements in coal except organically combined C, H, O, N and S are classified by this definition as mineral matter. This adequately classifies most inorganic elements in coals, those that are structurally bound within various minerals, but some other elements are also combined in the organic matter. The mineral matter of coal primarily includes clays, shales, pyrite, quartz, calcite and lesser amounts of other materials, depending on the chemical and mineralogical composition. It occurs in many forms and sizes, which may be seen by the naked eye or occur in micron-sized particles that require an optical or electron microscope to observe. The amount and composition of the mineral matter content can influence the combustion characteristics of coal. In recent years the application of derivative thermogravimetry (DTG) to the study of solid fuels has gained a wide acceptance amongst researchers in the field of energy conversion. The thermal analysis technique of thermogravimetry (TG) is one of in which the change in sample mass (mass-loss or gain) is determined as a function of temperature and/or time. Three modes of thermogravimetry are commonly used: a. Isothermal thermogravimetry, in which the sample mass is recorded as a function of time at constant temperature, b. Quasi-isothermal thermogravimetry, in which the sample is heated to constant mass at each of a series of increasing temperatures, and xvi c. Non- isothermal thermogravimetry, in which the sample is heated in an environment whose temperature is changing in a predetermined manner, preferably at a linear rate. Non-isothermal thermogravimetry has been widely used for evaluating burning properties of coals and chars. A plot of the rate of weight loss against temperature while burning a sample in air has been referred to as a "burning profile". Burning profiles obtained under a set of standard conditions provide detailed information from the onset of oxidation to complete burnout and are useful for predicting the relative ranking of fuels with regard to their combustion reactivities. Fuels with similar burning profiles have comparable burning characteristics in large coal-fired furnaces. The purpose of this study was to examine the effect of the mineral matter on the combustion properties of 25 Turkish lignite samples from various parts of Turkey and peat, bituminous coal and anthracite samples. The samples are from: XVll Thermogravimetric analysis was carried out using a Shimadzu TG 4 1 thermal analyzer to characterize the combustion of the coal and char samples. 40 mg coal samples ground to pass a 0.25 mm sieve were spread uniformly on the bottom of the crucible made of alumina. The flow rate of air was fixed at 40 cc/min. The temperature was raised with a heating rate of 40 K/min to 1273 K and held for 30 minutes at this temperature. The char samples were produced by heating the lignite samples in nitrogen up to 1423 K; after cooling to room temperature they were combusted in air under identical conditions of the coal samples. The demineralization of the lignite samples was performed by treatment with hydrochloric and hydrofluoric acids. A computer program in BASIC which enables regression analysis and determination of kinetic parameters from experimental thermogravimetric data, was used to calculate kinetic parameters of the combustion reactions. The kinetic parameters of combustion reactions were evaluated using six different methods of calculations: a) Horowitz-Metzger b) Dharwadkar-Karkhanavala c) Coats-Redfern d) Doyle modified by Zsako e) Single Heat Rate Integral Method f) Single Heat Rate Differential Method 20 different model equations were considered. It was found that the model equations were only changed depending on the calculation method used. However, the activation energy values which listed in Table 1 were affected both from sample properties and method of calculation used. The combustion profiles of the original and demineralized lignites, and of the char samples produced from them were compared and dicussed. The combustion profiles of the peat, bituminous coal and anthracite samples were also discussed. Results clearly show that the mineral matter content and the morphology of the coal samples play an important role in determining their combustion properties. The effects of Ca, Mg, Na,K,Si and Al contents of the coal and char samples on their combustion chacteristcs were compared.
The Effect of mineral matter content of coal on its combustion properties
Tez (Doktora)--İTÜ Fen Bil. Enst., 1999.
Keywords: Enerji; Kömür; Linyit; Yanma; Energy; Coal; Lignite; Combustion